Knocking The Door Strategies to Increase Covid-19 Vaccination Coverage for The Elderly in The Work Area of UPTD Puskesmas Bogor Tengah - Karina Amalia (Fakultas Kesehatan Masyarakat Universitas Muhammadiyah Jakarta, 2021)
The COVID-19 vaccination aims to reduce the transmission of COVID-19, reduce morbidity and mortality due to COVID-19, achieve herd immunity, and protect the community from COVID-19 to remain socially and economically productive. UPTD Puskesmas Bogor Tengah has entered the Covid-19 vaccine service targeting the elderly from March 30 to April 10, 2021, but the coverage is still low. Coordination with cross-sectors, RT, and RW administrators has been carried out and the result is that there are no more elderly people in the area who are willing to be vaccinated. The purpose of this study was to know the effectiveness of the knock the door strategy in increasing the achievement of Covid 19 vaccination for the elderly at UPTD Puskesmas Bogor Tengah. The method used is the descriptive method. This study was used to interview and documentation for data collection. Data analysis using qualitative analysis. The results of the study showed an increase in achievement from previously no more elderly people who were willing to be vaccinated, after conducted a knock the door strategy the achievement increased. It can be concluded that efforts to increase the coverage of the Covid 19 vaccine for the elderly require a special communication strategy and approach because the elderly have different characteristics in receiving information. The door-knocking strategy is quite effective in increasing the Covid 19 vaccination achievement for the elderly at the UPTD Puskesmas Bogor Tengah.